Demystifying Muslim consumer religiosity: does sustainability matter in halal food industry? / Johari Abdullah ... [et.al.] - Abdullah, Johari; Abdullah, Firdaus (Dr.); Bujang, Saimi (Universiti Teknologi MARA Cawangan Sarawak, 2022)
The recent outbreak of COVID-19 has negatively impacted the global Islamic economy, including the Halal food industry. Despite the pandemic, the Halal food industry continues to survive due to the growing and diverse Muslim population. Thus,researchers focus has shifted to the global Muslim consumers, especially their religiosity. Over the past few years, substantial research has focused on the effect of religiosity in predicting behaviour. Nevertheless, current conceptualisation and operationalisation have limited understanding of the multidimensional nature of religiosity. As such, this scarcity may not reflect the entire phenomenon. This paper aims to identify the Muslim consumer religiosity factors concerning Halal food products. The findings from this study suggest five factors that contribute to Muslim consumer religiosity, including the socio-environmental aspects that are essential pillars of sustainability. This new finding suggests that future research explore the social and environmental responsiveness concerning Muslim consumers in order for Halal practitioners to develop sustainable strategies that cater to Muslim consumer preferences.